Bpjs Employment in a National Crisis: A Comparative Study of Social Protection for Formal and Informal Workers - Bukit, Nathasa Jannice; Sahla, Retno Naqiyyah; nugraha, Bayu; Saragih, Claura Monica (Socious Journal, 2026)
This study analyzes the disparities in social protection between formal and informal workers within the BPJS Employment program in Indonesia, particularly in the context of national crises and the labor market transformation towards the gig economy. The main issues examined include inequalities in access, benefit coverage, and policy implementation effectiveness, which tend to favor the formal sector, leaving informal workers facing challenges such as fluctuating income, low social security literacy, and administrative-digital barriers. The research employs a qualitative approach with a comparative study design, reviewing recent literature and policy documents, and applying thematic analysis to explore policy dynamics, participation patterns, and implementation challenges. Preliminary findings indicate that formal workers receive more comprehensive and stable protection through automatic contribution mechanisms managed by employers, while informal workers experience significant gaps due to less adaptive policy designs, self-contribution schemes, and structural barriers. Policy reforms that are more flexible, inclusive, and responsive to the characteristics of informal workers are needed to expand coverage and strengthen the national labor social protection system.